The Role of Surfactant Micelles on the Partitioning of Antioxidant and the Oxidative Stability of Oil-in-Water Emulsion - Posman Sibuea; Sri Raharjo; Umar Santoso; Zuheid Noor (Jurnal Teknologi dan Industri Pangan, 2008)
Lipid oxidation system in which the fat is dispersed as emulsion droplets is still not well understood, although a large number of food exist partially or entirely in the form of emulsions. Therefore, this study was intended to examine how surfactant micelles influence the partitioning of antioxidant and hydroperoxides and how it alter the oxidative stability of oil-in-water emulsion. To determine the ability of surfactant micelles upon the partitioning of antioxidant in oil-in-water emulsion, this type of emulsion, containing quercetin at 0, 25, 50, 75 and 100 ppm, were prepared with polyoxyethylene 100 stearyl ether (Brij 700) or polyoxyethylene sorbitan monolaurate (Tween 20) with acetate or phosphate buffer (pH 3.0 or 7.0). Structurally Birj 700 has 5 times longer polyoxyethylene groups than Tween 20. After preparation of the emulsion, surfactant micelles (0-2%) were incorporated into the continuous phase to give a final lipid concentration of 5%. Lipid oxidation rates, as determined by the formation of lipid hydroperoxides, decreased with increasing quercetin concentrations. At pH 3, the peroxide value was higher than that at pH 7. Brij 70 decreased production of lipid hydroperoxides from palm oil-in-water-emulsions compared to the emulsions stabilized by Tween 20. the result showed that solubilization of quercetin into the aqueous into the aqueous phase by Brij or Tween micelles did not alter the oxidative stability of palm oil-in-water emulsion, suggesting that surfactant micelle influenced the oxidation rate by mechanism other than antioxidant solubilization. Key word : Quercetin, surfactant micelles, and oxidative stability